The Impact of Synchronous and Asynchronous Learning on Academic Integrity Violations by University Students - Prihatiningtias, Yeney Widya; Rahmat, Muhammad Aldi Alif (AIBPM Publisher, 2023)
This study intends to investigate the impact of synchronous and asynchronous online learning on the occurrence of academic ethical infractions among students. The object of this research is an active student of Bachelor's Degree in the Department of Accounting, Faculty of Economics and Business, Universitas Brawijaya. A total of 354 data were collected using a survey method with a purposive sampling technique. Data analysis was performed using the SPSS application. The test results show that synchronous online learning has an effect on students' academic ethics violations. In addition, the test results also show that asynchronous online learning has an effect on violations of student academic ethics. The findings are consistent with the Fraud Triangle Hypothesis, which contends that when fraud is possible, cases of academic ethical infractions become more serious.